Adoption of CRM technology in multichannel environment : a review (2000-2013) - Tiago, Flávio Borges (2013)
Despite the relevance of customer relationship management (CRM), there is a lack of a comprehensive literature review and a classification scheme for it in the last five years. This work provides an academic database of literature between the periods of 2000–2013, covering 28 journals and proposes a classification scheme to classify the articles in accordance to CRM main paths. Around fifty five hundred articles were identified and reviewed for their direct relevance to CRM in a multichannel environment. Eighty-seven articles were subsequently selected, reviewed and classified. Each of the selected papers was categorized on four CRM dimensions (Identification, Attraction, Retention and Development) and in the different channels involved (personnel sales, call center, email, web, and mobile). The review process was independently verified and promote interesting findings: Findings of this paper indicate that the research area of customer retention received most research attention during the first half of the years studied. On the other half, besides retention, development stage was truly relevant. Our analysis provides a roadmap to guide future research, as well as facilitate knowledge accumulation concerning the CRM in multichannel.